VD_FINDINFO AI 88/16 ap. TF - 103/2016 vom 20. April 2016 - VD Tribunal cantonal (2016)
DÉCISION SUR FRAIS, DÉPENS, TRIBUNAL FÉDÉRAL | 69 al. 1bis LAI, 61 let. a LPGA, 61 let. g LPGA, 49 LPA-VD, 55 LPA-VD